Effects of chemical treatments on seed germination and desiccation of wild banana (Musa acuminata colla ssp malaccensis and truncata) seeds for cryopreservation - Mohlisun, Zaitialia (2021)
Malaysia is one of the centers of diversity for bananas and plantain. Most of the edible banana available to date originated from the wild type namely Musa acuminata which is non-edible due to the large number of seeds within the pulp. It contains valuable genes and should be conserved. Although there are various methods of conservation, wild bananas produce seeds freely, thus conservation based on seeds would be the most cost effective. Despite being classified as orthodox, i.e., can tolerate desiccation to low moisture content and freezing the seeds are highly dormant, resulting in very low and erratic germination. This study was conducted to determine the effect of gibberellic acid (GA3), ethrel and acetone on wild banana seed germination. Secondly, this study determined the effect of desiccation on germination of wild banana seeds followed by the effects of desiccation and cryoprotectants on survival of wild banana embryos after cryopreservation. In the first part of the study, chemical treatments were used to break the dormancy and also to improve seed germination. Two ssp. namely Musa acuminata, malaccensis (low altitude type) and truncata (high altitude type) were studied. Freshly harvested wild banana seeds were pretreated with thirteen treatments namely control (no pretreatment, T1), ethrel (v/v); 0.01% (T2), 0.05% (T3), 0.1% (T4) and 0.5% (T5), GA3 (w/v); 0.02 %, (T6), 0.04 % (T7), 0.06% (T8) and 0.1 % (T9) and acetone (v/v); 10% (T10), 20% (T11), 30% (T12) and 40% (T13). Data on percentage of germination (G), mean germination time (MGT), germination index (GI) and percentage of embryo viability using tetrazolium test were recorded. There was no significant effect among the treatments on all parameters at P<0.05 for Musa acuminata ssp malaccensis. Higher germination percentage (26.5%) was observed when seeds were treated with 40% acetone (T13). The shortest time (MGT) for ssp malaccensis to germinate, was 11.93 weeks when treated with 0.1% ethrel (T4) and the longest time (MGT) to germinate was for T13, 20.72 weeks, almost 5 months. Speed of germination (GI), was higher when treated with 0.05% ethrel (T3), 5.19. However, there was a significant difference in the germination percentage of Musa acuminata ssp truncata, whereby seeds treated with ethrel 0.01% (T2) improved germination up to 93%, an increment of 26% compared to control. The shortest mean germination time (MGT), was 2.99 weeks when treated with 30% acetone (T12) and the longest MGT was for 0.1% ethrel (T4), 4.64 weeks. Speed of germination (GI) was higher when treated with 0.01% ethrel (T2), 99.44. In the second experiment, wild banana seeds were desiccated to understand the sensitivity of wild banana seeds to desiccation. Freshly harvested seeds of Musa acuminata ssp malaccensis and ssp truncata were desiccated to six target moisture contents (TMC); 40, 30, 20, 15, 10 and 5% followed by germination in sand and seed moisture content (MC), percentage of seed germination (G), mean germination time (MGT), germination index (GI) and percentage of survival for the embryo culture were recorded. The germination of Musa acuminata ssp. truncata seeds was relatively high, with more than 84%. However, excessive desiccation to below 10% moisture, reduced germination to 58.5%. Finally, in the third experiment, as an alternative the embryo was removed from the surrounding chalazal mass to obtain high germination. This option allowed the use of zygotic embryo for conservation of wild banana via cryopreservation. The zygotic embryos were excised aseptically and subjected to three cryoprotectants (MS-basal, 0.5 v/v% DMSO and 0.5 w/v% sucrose), a control without any cryoprotectant was also included in the experiment, prior to liquid nitrogen exposure. Upon thawing, the embryos were cultured onto MS medium and evaluated for survival. Pretreatment with only basal media was sufficient to enhance desiccation tolerance and survival in LN up to 80% as compared to without cryoprotectant, which had 50% survival. Musa acuminata ssp malaccensis was tolerant to desiccation but hindrance to germination prevails. This study demonstrates the germination potential and feasibility of long term preservation of M. acuminata ssp. malaccensis and M. acuminata ssp. truncata embryo by cryopreservation. In conclusion, Musa acuminata ssp. malaccensis is very dormant and chemical enhancer is not effective in overcoming their dormancy. Germination of Musa acuminata ssp. truncata was significantly high with control giving 74%, while addition of ethrel at 0.01% improved germination up to 90%. Musa acuminata ssp. truncata is tolerant to desiccation. Embryo rescue technique improved germination of Musa acuminata ssp. malaccensis. Desiccation is an important factor, which can determine the survival of banana embryos cryopreserved in liquid nitrogen. Pretreatment with only basal media can enhance desiccation tolerance and survival in liquid nitrogen up to 80%.